2012
DOI: 10.1152/ajpgi.00111.2012
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of biochemical, molecular, and physiological changes accompanying bile acid pool size restoration in Cyp7a1−/−mice fed low levels of cholic acid

Abstract: Jones RD, Repa JJ, Russell DW, Dietschy JM, Turley SD. Delineation of biochemical, molecular, and physiological changes accompanying bile acid pool size restoration in Cyp7a1 Ϫ/Ϫ mice fed low levels of cholic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…This was also the case in Cyp7a1 −/− mice maintained on a low-cholesterol diet containing either CDCA (Fig. 3C) or CA [31]. …”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…This was also the case in Cyp7a1 −/− mice maintained on a low-cholesterol diet containing either CDCA (Fig. 3C) or CA [31]. …”
Section: Resultsmentioning
confidence: 61%
“…Relative mRNA levels in individual animals were determined by expressing the amount of mRNA found relative to that obtained for Cyp7a1 +/+ mice fed the basal diet alone (all studies with males), or the basal diet enriched with cholesterol (studies with females), which in each case was arbitrarily set at 1.0. The primer sequences used to measure RNA levels for all genes have been reported in two earlier publications [31, 38]. The names of all genes studied are as follows; Cyp7a1, Cholesterol 7α-hydroxylase; Cyp27a1, Sterol 27-hydroxylase; Cyp39a1, Oxysterol 7α-hydroxylase; Cyp7b1, Oxysterol 7α-hydroxylase; Cyp8b1, Sterol 12α-hydroxylase; Abca1, ATP binding cassette member A1; Abcb11, Bile salt export pump (Bsep); Abcg5, ATP-binding cassette G5; Fabp6, Ileal bile acid binding protein (Ibabp); Fgf15, Fibroblast growth factor 15; Hmgcs, Hydroxymethylglutaryl coenzyme A synthase; Npc1l1, Niemann-Pick Type C1 -like 1; and Nr0b2, Short heterodimer partner (Shp).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice had low survival rates and required vitamin supplementation to reach adulthood, and had reduced bile acid pool size, reduced fecal excretion of bile acids, and reduced fecal sterol and intestinal cholesterol absorption. It was also more recently reported that Cyp7a1 / mice exhibited induction of Cyp8b1 gene expression and repression of genes involved in the alternative synthesis pathway, and that these mice were physiologically responsive to low-dose CA and CDCA supplementation (19,20). The mice used in the present study were obtained by backcrossing the mixed background B6/129Sv strain with C57BL/6J mice for seven generations to obtain a nearly pure C57 background and represent a model suitable for use in dietary studies.…”
Section: Discussionmentioning
confidence: 85%
“…The original adult Cyp7a1 / mice in the mixed genetic background (B6/129Sv) had a reduced bile acid pool (30% of WT mice) and a normal lipid profile, while a later study of the same Cyp7a1 / mice (B6/129Sv) in a different colony demonstrated improved survival and a milder phenotype (18), though females in this colony were hypercholesterolemic. Two recent studies using the original Cyp7a1 / mice (B6/129Sv) demonstrated that even low dose bile acid feeding could rescue the knockout phenotype (19,20). These studies also reported that Cyp8b1 gene expression was upregulated in Cyp7a1 / mice (B6/129Sv), while genes involved in the alternative bile acid synthesis pathway were not, despite increased oxidized sterol content.…”
Section: Metabolic Analysismentioning
confidence: 99%